AANPASSINGSPROBLEME IN DIE MILITERE MILIEU - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
In order to adapt successfully to the military milieu, a soldier is required to arrange his personal values and disposition in accordance with the demands of that particular milieu. Selfdenial and total identification with the group are required of a good soldier. He must also always be correctly motivated as sincere belief in the purpose and necessity of a war is the most important component for the creating of esprit de corps, which in turn can greatly influence the soldier’s performance on the battlefield. This article is a thoroughly researched attempt to analyse the soldiers’ problems in adapting to a military milieu and to offer possible solutions to some of these problems.